The elements of style. - Strunk, William 1869-1946.; White, E. B. (Elwyn Brooks) 1899-1985. (Boston Allyn and Bacon, 2000)
This classic reference is a must-have for any student or writer. In this brief handbook, Strunk identifies the principal requirements of proper American English style and concentrates on the most often violated rules of composition. Authoritative and engagingly written, this is simply the greatest book of its kind.
I. Elementary Rules of Usage -- II. Elementary Principles of Composition -- III. A Few Matters of Form -- IV. Words and Expressions Commonly Misused -- V. An Approach to Style (With a List of Reminders)
Previous ed.: Boston, Allyn and Bacon, c2000.
Includes index.
UCASM-1710 (UCASM001710)
Keywords: English language -- Rhetoric; English language -- Style; Report writing